Strategies of Politeness Found in “Rich Teen Shame Girl at Thrift Store” Short Film: Pragmatics Approach - Icha Sartika; Mhd. Johan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aimed to identify politeness strategies in Rich Teen Shame Girl at Thrift Store. The research design of this research is qualitative descriptive. The data were collected by using an observational method and a non-participatory technique. The data were analyzed using the practical identity method and pragmatic competence-in equalizing. The data source in this study is Rich Teen Shame Girl at Thrift Store short films. This study showed that there were 15 data of politeness by the characters in the short film. There were 2 data on record found in the short film, 9 data of positive politeness, 2 data of negative politeness, and 1 data showed off-record. Rich Teen Shame Girl's positive politeness strategy was more dominant in Thrift Store short film. In conclusion, politeness strategies, namely bald on record, positive politeness, negative politeness and off-record. Positive politeness was the most frequently used strategy of politeness. Keywords: Pragmatics, Politeness, Short film